Long-Term Effects of Single and Repeated Ketamine Infusions on Treatment-Resistant Depression: A Retrospective Chart Review Study - Sofia Sakopoulos; Lisa D. Hinz (Psychoactives)
Treatment-resistant depression (TRD) is a substantial public health burden with limited treatment options. Recent evidence suggests that single and repeated-dose ketamine infusions have rapid and significant antidepressant effects on individuals with TRD. Few studies have compared single or repeated (6) ketamine infusions past 14 days post-treatment. This retrospective chart review study investigated the long-term effects of single (n = 9) and repeated (6) (n = 5) high-dose (1 mg/kg) intravenous ketamine infusions on TRD 30 days post-infusion(s) (N = 14). Changes in depressive symptoms were measured by comparing Beck Depression Inventory (BDI-II) scores pre- and 30 days post-treatment for an understanding of long-term efficacy in clinical practice. Results indicated that ketamine has the potential to be an effective and enduring intervention for TRD, adding treatment and management options that are currently limited.